An Integrated Perspective : The Impact of Digital Financial Knowledge and Self-Esteem on Financial Behavior in the Lives of College Students - Azaria, Candra; Susilaningsih, Susilaningsih; Sudarno, Sudarno (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to analyze the impact of digital financial knowledge on college students’ financial behavior, and the involvement of self-esteem as a mediator variable. This study used a quantitative survey method. The sample used was a group of 249 undergraduate students majoring in accounting education at Universitas Sebelas Maret and Universitas Negeri Semarang. A conceptual model, containing hypotheses outlining the impact was constructed and assessed through validity, reliability, frequency statistics and path analysis. The findings indicated a direct and positive correlation of digital financial knowledge on financial behavior. This research contributes fresh perspectives by providing both practical and theoretical insights into the variables employed in the study.